Multifocal Mycobacterium kansasii osteomyelitis in a patient on ruxolitinib. (January 2022) - Pan, Liyang; Lever, Elliott; Ma, Jianfei; Beynon, Huw; Brown, Michael; Manson, Jessica
Highlights: The presence of non-caseating granulomas on biopsy does not preclude mycobacterial infection, and should trigger careful investigation. JAK inhibitors such as ruxolitinib increase the risk of mycobacterial infections, making specific investigations critical to diagnostic certainty. M. Kansasii infection in bones and joints is rare, and is mainly found in immunosuppressed patients. Biopsy and culture including specifically for mycobacteria should be initiated if there is any clinical suspicion. Abstract: Background: Mycobacterium kansasii spinal infection is rare. This is the first reported case in a patient taking ruxolitinib. Case report: A 69-year-old woman attended the emergency department with severe debilitating lumbar back pain and right sided flank pain. She had experienced persistent right lower chest wall pain following 4 weeks of coryzal symptoms but denied fever or weight loss. She was being treated with ruxolitinib for myelofibrosis. C reactive protein was 9 mg/L. CT and MRI showed bilateral hilar and mediastinal lymphadenopathy, and lytic lesions in the T10 vertebral body and left iliac bone. Noncaseating granuloma were found on endobronchial ultrasound guided lymph node biopsy and on biopsy of the iliac crest, with sarcoid considered a possible diagnosis. Results: On two occasions the patient had pain so severe that she required hospitalisation. Pulsed intravenous corticosteroids was given with symptomatic improvement. Iliac bone biopsy grew Mycobacterium Kansasii at 6-week culture. The patient completed 12 months of treatment (12 months rifampicin and isoniazid, 6 months ethambutol), with resulotion of pain. Conclusion: We present a challenging case of mycobacterial osteomyelitis where there was initial diagnostic uncertainty. Sarcoidosis can involve multiple bony lesions but would not typically cause a spondylodiscitis. A recent pharmacovigilance report highlights that JAK inhibitors such as ruxolitinib increase the risk of mycobacterial infections, making specific investigations critical to diagnostic certainty.